Situational Crime Prevention: Theoretical Background and Possibilities for Further Development (Kriminalističke teme, 2017)
Inspiration and issue(s) that are addressed: Situational Crime Prevention is part of the Crime Prevention Policy and in recent years, it’s proponents strive to replace the social prevention as unsuccessful in crime reduction, too expensive and too demanding to tackle the social criminal factors. That way, a group of criminologists claims that prevention from distance doesn’t work and redirect their interest toward removing the situational factors that make opportunities for crime. In that regards, our article will elaborate the basis and main findings related to the benefits and possible risks of situational crime prevention.Purpose of the paper (scientific and and/ or social): The aim of the paper is to present the pros and cons of the application of situational crime prevention. The scientific and social objective to study this model of crime prevention stems from the need that the wider crime policy should encompass, not just the repressive measures, but also preventive, and not just undertaken by the criminal justice system, but beyond and by the agencies within civil society and private sector.Methodology/ Design: This paper provides an overview and analysis of certain scientific papers and studies that present research findings and results related to situational crime prevention. Also, we will go through several criminological theories and perspectives within the environmental criminology, in order to present theoretical background of situational crime prevention.Limitations of the study/ paper: Lack of public and scientific discourse, as well as unrecognition of the importance of situational crime prevention among criminal justice policy makers in our country.Results/ Findings: Main findings refer to the recognition of the benefits of situational crime prevention, but also of certain negative sides that demand careful application and selection of certain prevention measures by the main stakeholders.General conclusion: Situational Crime Prevention may reduce crime in certain circumstances, but cannot solve the crime problems, i.e. cannot decrease or remove the criminal factors. That way, it can be part of the general national crime prevention policy, but only together with the social prevention, because those two are like two sides of one coin.Justification of study/ paper: Research and situational crime prevention in the Republic of Macedonia should be subject to continuous analysis. Science, based on scientific research and results should help to promote the positive effects of its application in order to find its appropriate place within criminal justice policy.